1981
DOI: 10.1177/00220345810600060501
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and Inhibitory Effects of Substance P on Rat Submandibular Secretion

Abstract: Intravenous infusions of the undecapeptide substance P caused a moderate but transient secretory response from the rat submandibular gland. The electrolyte composition of the saliva elicited by this peptide was qualitatively similar to that of the secretion induced by parasympathomimetic agents. Substance P inhibited the secretory response to acetylcholine and isoproterenol, but did not modify the binding of specific ligands to glandular autonomic receptors. It is concluded that this naturally occurring peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Treatment with 10 jxmollL SP also resulted in a decrease in SM secretion, similar to that reported by Ekstrom et al (1983), which may possibly be due to a decrease in receptor sensitivity (Strittmatter et al, 1977), resulting from the exposure of the gland to a supra-maximal concentration (10 jxmol/ L = 8.12 ,ug/kg/min) of SP. The profiles of protein and calcium produced in the present study were similar to those obtained with cholinergic stimulation (Martinez and Martinez, 1981;Yu et al, 1983) bition of SP-induced salivary secretion with higher doses of atropine (5-100 gg/kg and 2 mg/kg) than were used in the current study. The larger doses of atropine employed in their studies may have resulted in non-selective blockade of the SP response.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Treatment with 10 jxmollL SP also resulted in a decrease in SM secretion, similar to that reported by Ekstrom et al (1983), which may possibly be due to a decrease in receptor sensitivity (Strittmatter et al, 1977), resulting from the exposure of the gland to a supra-maximal concentration (10 jxmol/ L = 8.12 ,ug/kg/min) of SP. The profiles of protein and calcium produced in the present study were similar to those obtained with cholinergic stimulation (Martinez and Martinez, 1981;Yu et al, 1983) bition of SP-induced salivary secretion with higher doses of atropine (5-100 gg/kg and 2 mg/kg) than were used in the current study. The larger doses of atropine employed in their studies may have resulted in non-selective blockade of the SP response.…”
Section: Discussionsupporting
confidence: 80%
“…The existence of SP receptors in both the SM and PAR glands (Bahouth and Musacchio, 1985;Putney, 1977) and the profile of secretion observed in the present study also suggest that SP must have some physiologically relevant function similar to that produced by cholinergic stimulation in rat salivary glands. Consequently, the presence of specific receptors for SP (and other related peptides) in rat salivary glands might possibly represent a modulatory or physiological mechanism to ensure glandular responsiveness when the neural (cholinergic) pathway is blocked or inhibited (Martinez and Martinez, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…33 Substance P opens the K conductance pathway in the basolateral membrane of salivary acinar cells 12 and induces K efflux. 63 Recent evidence from our laboratory has also shown that this peptide induces a net 36 C1 efflux from tracer preloaded submandibular acini 54b similar to that induced by acetylcholine.…”
Section: B Other Bioactive Substances Which Induce Salivationmentioning
confidence: 99%
“…Several types of neurotransmitters or regulatory factors play a role in the control of salivary gland secretion including not only noradrenaline and acetylcholine, but neuropeptides such as substance P (SP) and vasoactive intestinal polypeptide (VIP) [7,10]. Substance P, a member of the tachykinin family, induces water and electrolyte secretion in the salivary glands [11][12][13]. Vasoactive intestinal polypeptide, on the other hand, is a member of the glucogen peptide family and evokes the release of a small volume of saliva that is rich in protein [14,15].…”
Section: Introductionmentioning
confidence: 99%